Availability assessment of oil and gas processing plants operating under dynamic Arctic weather conditions. (August 2016) - Naseri, Masoud; Baraldi, Piero; Compare, Michele; Zio, Enrico
Abstract: We consider the assessment of the availability of oil and gas processing facilities operating under Arctic conditions. The novelty of the work lies in modelling the time-dependent effects of environmental conditions on the components failure and repair rates. This is done by introducing weather-dependent multiplicative factors, which can be estimated by expert judgements given the scarce data available from Arctic offshore operations. System availability is assessed considering the equivalent age of the components to account for the impacts of harsh operating conditions on component life history and maintenance duration. The application of the model by direct Monte Carlo simulation is illustrated on an oil processing train operating in Arctic offshore. A scheduled preventive maintenance task is considered to cope with the potential reductions in system availability under harsh operating conditions. Graphical abstract: Arctic harsh climatic conditions adversely affect the performance of offshore oil and gas processing plants. Modelling time-dependent effects of such environmental conditions on the components failure and repair rates and analysing their associated uncertainties are of particular importance in plant decision-making processes such as setting a preventive maintenance policy. Highlights: Availability of Arctic offshore oil and gas processing facilities is analysed. Arctic environmental conditions can extend downtimes and increase failure rates. Dynamic effects of Arctic weather conditions on plant availability are modelled. Availability of an oil and gas plant is analysed under preventive maintenance.